Past, present, and future of mergers and acquisitions in the MENA region: a systematic review and integrative framework - Battisti, Enrico; Christofi, Michael; Vrontis, Demetris; Nirino, Niccolò (My University, 2021)
Although the business strategies of mergers and acquisitions (M&As) are investigated theoretically and practically, their diffusion and features in the Middle East and North Africa (MENA) region are not clearly described in the literature. This is in particular due to the recent transformation that member countries have been going through since the financial crisis of 2008 and the Arab Spring. Through shareholder maximization theory, agency theory, and the resource-based view we identified the reasons and characteristics of M&As in the Middle East and North Africa regions. Following a systematic literature review methodology, we identified 37 articles related to M&A in MENA countries published in peer-reviewed journals and reported in CABS ranking (Chartered Association of Business Schools). Based on this analysis, we map the extant literature on the topic and present an integrative framework of these features for future researchers to further explore and expand the boundaries of the domain.
Keywords: Mergers and acquisitions; MENA region; Systematic literature review; Integrative framework